The Development of Canva-Based Media to Improve Language Literacy - Ratih Rindyani; Asri Yulianda; Rizki Lestari (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to develop Canva-based learning media to improve language literacy of grade VII students of SMPN2 Bilah Barat. The learning media developed is expected to provide a more interesting and interactive learning experience, as well as improve students' language literacy skills. The research method used is Research and Development (R&D) with the Borg and Gall development model. The subjects of this study involved grade VII students of SMPN2 Bilah Barat who were tested using test instruments and questionnaires. The results of the study showed that the Canva learning media developed can improve students' motivation and language literacy skills, with an average expert validation score reaching 94.53, which is classified as very good. In addition, the results of the field test showed a significant increase in students' language literacy skills after using Canva media, with t-test data showing a significant difference between the pretest and posttest results with a difference of 11.74. Based on these findings, Canva media has proven effective in improving students' language literacy, so it can be used as an alternative in language learning in grade VII of SMPN2 Bilah Barat